HIGHER EDUCATION STUDENTS’ FOREIGN LANGUAGE ANXIETY: A CASE STUDY AT ENGLISH EDUCATION DEPARTMENT OF IAIN LANGSA - Shafrida Wati; Nina Afrida (Jurnal Education and Development, 2022)
This study discusses EFL learners’ foreign language anxiety at a higher education institution in Langsa. It further explores factors that contribute to language apprehension and how it manifests in the students. This study employed a qualitative approach with the type of case study research. The subjects of this research were 10 students of the English Education Department of IAIN Langsa. The data were collected through observation, focus group discussion, and in-depth interviews. Data analysis techniques included data reduction, data presentation, and data conclusion. This study found that the majority of the students experienced anxiety in learning English as a foreign language. Factors that trigger anxiety include inadequate vocabulary and knowledge of grammar, unintelligible pronunciation, individual learning preferences, and afraid of negative evaluation. Some learners suffered various symptoms when practicing the target language, such as shaky hands, wobbly legs, stuttering, headache, and a sense of dread. Such factors affected their attitudes toward the foreign language learning, such as language inhabitant, demotivated, and worried in language classrooms. Nevertheless, few of them conducted efforts to deal with the anxiety include participating in the classroom activity, preparing notes before speaking, and learning with peers.